2022
DOI: 10.3390/fishes7010043
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling Revealed Basis for Growth Heterosis in Hybrid Tilapia (Oreochromis niloticus ♀ × O. aureus ♂)

Abstract: Hybrid tilapia were produced from hybridization of Nile tilapia (Oreochromis niloticus) and blue tilapia (O. aureus). Comparative transcriptome analysis was carried out on the liver of hybrid tilapia and their parents by RNA sequencing. A total of 2319 differentially expressed genes (DEGs) were identified. Trend co-expression analysis showed that non-additive gene expression accounted for 67.1% of all DEGs. Gene Ontology and KEGG enrichment analyses classified the respective DEGs. Gene functional enrichment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…In a previous study conducted by Xu et al [42], it was found that hybrid tilapia inherited all of the lactate dehydrogenase isoenzyme bands from parent Nile tilapia and only some of the lactate dehydrogenase isoenzyme bands from parent blue tilapia during electrophoresis. Similarly, Zhong et al [19] observed that GH genes exhibited asymmetric expression in hybrid tilapia, with the expression of the maternal sub-genome from Nile tilapia dominating in hybrid tilapia under both feeding and fasting conditions.…”
Section: Role Of Cis-acting Element Variants In P38 Allele-specific E...mentioning
confidence: 92%
See 1 more Smart Citation
“…In a previous study conducted by Xu et al [42], it was found that hybrid tilapia inherited all of the lactate dehydrogenase isoenzyme bands from parent Nile tilapia and only some of the lactate dehydrogenase isoenzyme bands from parent blue tilapia during electrophoresis. Similarly, Zhong et al [19] observed that GH genes exhibited asymmetric expression in hybrid tilapia, with the expression of the maternal sub-genome from Nile tilapia dominating in hybrid tilapia under both feeding and fasting conditions.…”
Section: Role Of Cis-acting Element Variants In P38 Allele-specific E...mentioning
confidence: 92%
“…These studies have made some progress and helped us to understand the mechanism of MAPK's role in fish. In our previous study, transcriptome analysis revealed that p38 showed non-additive expression in hybrid tilapia and played a key role in multiple enriched pathways such as the endocrine system, disease immunity, and the oxidative metabolism [25,26]. Hu et al [3] found that, in Nile tilapia and hybrid tilapia, S. agalactiae infection can activate the p38 MAPK pathway, and the rapid response and high level of protein expression of p38 MAPK may be the reason why hybrid tilapia have stronger bacterial resistance than Nile tilapia.…”
Section: Introductionmentioning
confidence: 99%
“…Ribosome biogenesis in eukaryotes includes the maturation of ribosomal RNA and assembly into ribosomal subunits [45]. Ribosome biogenesis determines the rate of protein synthesis and regulates the accumulation of cell mass or cell growth by controlling the major anabolic cellular processes [46]. The endoplasmic reticulum is involved in protein synthesis, folding, and processing and directs misfolded proteins to the proteasome for degradation [47].…”
Section: Effects Of High Stocking Density On Protein Metabolism-relat...mentioning
confidence: 99%
“…ACACA is involved in the first step of fatty acid synthesis and is also a key rate-limiting enzyme in this reaction, facilitating the catalytic conversion of acetyl CoA to malonyl CoA [71,72]. Subsequently, malonyl CoA undergoes successive condensation reactions with acetyl CoA in the presence of FASN, another key rate-limiting enzyme for fatty acid synthesis, to produce long-chain saturated fatty acids [46,71]. SCD1 and FADS2 exhibit fatty acid desaturation activity, wherein they can convert long-chain saturated fatty acids into their unsaturated counterparts.…”
Section: Effects Of High Stocking Density On Lipid Metabolism-related...mentioning
confidence: 99%
“…The Nile tilapia (♀) × blue tilapia (♂) hybrid is one of the most popular farmed tilapia varieties in China, due to its fast growth performance and strong resistance to low temperature ( 28 ). This tilapia variety also showed higher appetite ( 29 ).…”
Section: Introductionmentioning
confidence: 99%